The law and practice of peacekeeping : foregrounding human rights / Rosa Freedman, Nicolas Lemay-Hébert, Siobhán Wills. - Freedman, Rosa; Lemay-Hébert, Nicolas; Wills, Siobhán (Cambridge University Press, 2021)
In an increasingly complex world, it is more crucial than ever to have a full picture of how international peacekeeping can be a force for good, but can also have potentially negative impacts on host communities. After thirteen years of presence in Haiti, the highly controversial United Nations Stabilization Mission in Haiti has now withdrawn. The UN's legacy in Haiti is not all negative, but it does include sexual scandals, the divisive use of force to 'clean up' difficult neighbourhoods as well as a cholera epidemic, brought inadvertently by Nepalese peacekeepers that killed more than 8,000 Haitians and infected more than 600,000. This book presents a unique multi-disciplinary analysis of the legacy of the mission for Haiti. It presents an innovative account of contemporary international peacekeeping law and practice, arguing for a new model of accountability, going beyond the outdated immunity mechanisms to foreground human rights.